Monitoria na escola do campo: alunos ajudando alunos na aprendizagem da matemática - Câmara, Dieyson (2017)
This research brings a monitoring experience with elementary school students in a rural school in the municipality of Capanema, state of Paraná, Brazil. We held meetings with students from two classes (6th grade and 9th grade) where students from the 9th grade helped 6th grade students to solve a list of activities related to basic mathematical operations involving natural numbers. The activities were elaborated following concepts of Ethnomathematics, defended by authors like D'Ambrosio (1993; 2002), Ribeiro, Domite and Ferreira (2006). The main objective of this research was to investigate the contributions, positive or negative, that the monitoring activity can provide in relation to mathematics learning.